The Paranormal is (Still) Normal: The Sociological Implications of a Survey of Paranormal Experiences in Great Britain. (September 2014) - Castro, Madeleine; Burrows, Roger; Wooffitt, Robin
Historically, there has been limited sociological interest in the paranormal and no systematic study of reported paranormal experiences. There are also few medium-to-large-scale survey results with nationally representative populations focusing on paranormal experiences . This paper provides details of an exploratory survey conducted in 2009 with a nationally representative sample of 4, 096 adults aged 16 years and over across Great Britain [1] . Our findings show that 37% of British adults report at least one paranormal experience and that women, those who are middle-aged or individuals resident in the South West are more likely to report such experiences. These results establish incidence levels of reported paranormal experiences in contemporary Britain. We argue also that they merit a more sustained sociological consideration of the paranormal. In this respect we renew and update the robust justification and call for serious research positioning the paranormal as a social phenomenon, originally proposed well over thirty years ago byGreeley (1975) .